Evaluation of a diagnostic algorithm for Heparin-Induced Thrombocytopenia. Issue 152 (April 2017) - Farm, Maria; Bakchoul, Tamam; Frisk, Tony; Althaus, Karina; Odenrick, Alice; Norberg, Eva-Marie; Berndtsson, Maria; Antovic, Jovan P.
Abstract: Introduction: Heparin-Induced Thrombocytopenia (HIT) is a rare but serious immune-mediated complication of heparin treatment. HIT is characterized by an acute, transient prothrombotic state combined with thrombocytopenia and is caused by platelet-activating IgG antibodies that bind to complexes of heparin and platelet factor 4. The diagnosis of HIT relies on clinical presentation and the demonstration of HIT antibodies. One approach to improve the efficacy of laboratory analysis is to use a diagnostic algorithm. Aim: To evaluate one diagnostic algorithm for HIT where the 4 T's clinical risk score is combined with immunochemical and/or functional assays. Materials and methods: The quality of the diagnostic algorithm was retrospectively evaluated in 101 patients with suspected HIT. Laboratory results obtained from the diagnostic algorithm were compared to Heparin-Induced Platelet Aggregation (HIPA) and clinico-pathological evaluation of patients' medical records. Results: We found that the algorithm had a diagnostic efficacy of 94%, with specificity of 94% and sensitivity 94%. Positive likelihood ratio (LR +) was 16.0, and the negative likelihood ratio (LR −) 15.5. The efficacy of PaGIA ( n  = 95) was 0.46, and IgG-specific HPF4-abELISA ( n  = 54) was 0.87. Conclusions: The diagnostic algorithm for HIT is sufficiently accurate and leads to in overall faster results and decreased cost of analysis. The weakest link of the algorithm is the risk of miscalculated 4 T's scores, which is inevitably exacerbated by the insufficient experience most clinicians have with HIT. This highlights the importance of clear instructions from the laboratory and coagulation clinic. Highlights: The diagnostic algorithm is more accurate and safe than any single HIT assay alone. Use of the algorithm means the decision about an interruption of heparin need not be delayed. The diagnostic algorithm for HIT enables more effective use of laboratory resources. Miscalculation of 4 T's scores has a big impact on interpretation of the final laboratory results. The inexperience with HIT that most clinicians have entails a risk of miscalculation of 4 T's scores.